[OP.7D.05] NEED FOR FOREARM BLOOD PRESSURE REFERENCE VALUES AT HEART LEVEL. (September 2017) - Stojanovic, M.; Nisic, T.; Ciric, J.; Stojkovic, M.; Savic, S.; Beleslin, B.; Parapid, B.; Stojanov, V.; Zarkovic, M.
Abstract : Objective: The increasing number of obese people presents a very serious clinical challenge to doctors being faced with the inaccurate measuring blood pressure (BP) in patients with very large arms. Studies comparing forearm and upper-arm cuff occlusion have given conflicting results. It is likely that higher BP readings are obtained with forearm measurement. Our clinic took part in the International Ambulatory Blood Pressure Registry: Telemonitoring of Hypertension and Cardiovascular Risk Project (ARTEMIS). In order to obtain normal values of forearm blood pressure at heart level in population we analyzed sample of patients with normal ambulatory blood pressure monitoring (ABPM) values. Design and method: Two hundred and fifty-eight patients with normal ABPM values were studied from the ARTEMIS project. Mean body mass index was 24 +/−7 kg/m 2 . Before positioning the Meditech ABPM 05 device patients had three upper-arm and three forearm BP taken by Meditech ABPM 05 device using extra measurement option. Arm was supported at heart level and appropriate cuff was used. Mean BP was calculated from three BP consecutive measurements. Student's t-test was used to analyze the data. Results: Systolic and diastolic upper-arm BP measurements were significantly lower than forearm BP measurements. The measurements obtained by ABPM were significantly lower than those found for forearm systolic and diastolic blood pressures. The mean age was 36.4+/−12.6 years. There were 152 females. Mean forearm, upper- arm and ABPM systolic BPs were 132.6 +/−18.5 mmHg, 127.3 +/−17.4 mmHg and 123.3 +/−15.6 mmHg respectively. Mean forearm, upper- arm and ABPM diastolic BPs were 84.8 +/−13.4 mmHg, 79.6 +/−12.4 mmHg and 74.8 +/−14.6 mmHg respectively. Conclusions: This study showed that we need forearm blood pressure reference values at heart level because there is significant difference between forearm and upper-arm BP measurements. More often doctors are faced with the inaccurate measuring BP in patients with very large arms.